Creativity and innovation in the work environment of technical and vocational courses teachers (Research, Society and Development, 2022)
The capacity for innovation, essential for business development in the contemporary context, is associated with the creative potential of its employees. In this sense, the identification of contextual factors that may enhance or inhibit creativity is important for organizations. Training professionals to work in this business context also requires innovative models and practices from educational institutions, having the teacher as an essential pillar in this process. Thus, it is important for technical and vocational education institutions to identify contextual factors that promote or inhibit the creativity of their teachers. The objective of this study was to analyze the relationship between factors of the work environment with the perception of creativity from the perspective of teachers of professional education. The KEYS® instrument was applied to 65 teachers from a technical and vocational education institution in Bahia. Responses were analyzed quantitatively using descriptive methods and Spearman's correlation test. The work environment factors showed statistically significant correlation with the perception of creativity. The participants made some suggestions to improve creativity and innovation as more training and development for the teachers, more recognition of teachers´ creative work, more access to educational tools, and having collaborative groups.